Hubungan Remunerasi, Retensi dan Kinerja Karyawan - Didit Darmawan; Devi Iriandha; Dian Indrianto; Dwi Sembe Sigita; Diah Cahyani (Journal of Trends Economics and Accounting Research, 2021)
The managerial practice of human resources to retain employees and develop performance is through a remuneration policy. This policy is a form of reward to employees for the contributions they make to their organization. Remuneration is one of the organization's strategies to empower the workforce, and can function as a company's competitiveness. Conformity between remuneration policies and employee recruitment will be the main factor in shaping the quality and competence of the organization's performance. This study aims to determine the extent to which remuneration has a relationship with employee retention and performance. This survey used a sample of 86 randomly selected respondents. Descriptive statistics involve frequency tables, while correlations are used to prove the relationship between variables. The study findings show that an effective remuneration policy has a strong relationship to improve employee performance. In addition, there is a significant relationship between remuneration and employee retention. Employees are possible to stay in the organization if the remuneration policy is in accordance with employee expectations